e-Banking Adoption: An Opportunity for Customer Value Co-creation - Carranza, Rocío; Díaz, Estrella; Sánchez-Camacho, Carlos; Martín-Consuegra, David (Frontiers in Psychology, 2021)
The development of Information and Communication Technologies offers innovative opportunities to establish business strategies focused on customer value co-creation. This situation is especially notable in the banking industry. e-Banking activities can support competitive advantages. However, the adoption of e-banking is not yet well-established among consumers. In this sense, the Technology Acceptance Model (TAM) is considered essential in studying consumer behaviour applied to adopt a particular technology. According to the TAM model, this study analyses the factors which influence bank customers to adopt e-banking to facilitate their banking services and support the process of value co-creation. Consequently, the authors examine five main aspects of the technology adoption model to provide a broad understanding of bank customers' consumption of e-banking. A Partial Least Squares Structural Equation Modelling (PLS-SEM) analysis is conducted to evaluate proposed relationships between factors and customers' e-banking adoption.